Drug Development for the Irritable Bowel Syndrome: Current Challenges and Future Perspectives - De Ponti, Fabrizio (Frontiers in Pharmacology, 2013)
Medications are frequently used for the treatment of patients with the irritable bowel syndrome (IBS), although their actual benefit is often debated. In fact, the recent progress in our understanding of the pathophysiology of IBS, accompanied by a large number of preclinical and clinical studies of new drugs, has not been matched by a significant improvement of the armamentarium of medications available to treat IBS. The aim of this review is to outline the current challenges in drug development for IBS, taking advantage of what we have learnt through the Rome process (Rome I, Rome II, and Rome III). The key questions that will be addressed are: (a) do we still believe in the “magic bullet,” i.e., a very selective drug displaying a single receptor mechanism capable of controlling IBS symptoms? (b) IBS is a “functional disorder” where complex neuroimmune and brain-gut interactions occur and minimal inflammation is often documented: do we need to target gut motility, visceral sensitivity, or minimal inflammation? (c) are there validated biomarkers (accepted by regulatory agencies) for studies of sensation and motility with experimental medications in humans? (d) do animal models have predictive and translational value? (e) in the era of personalized medicine, does pharmacogenomics applied to these medications already play a role? Finally, this review will briefly outline medications currently used or in development for IBS. It is anticipated that a more focused interaction between basic science investigators, pharmacologists, and clinicians will lead to better treatment of IBS.